Beberapa Masalah Muatan Materi UU No. 22 Tahun 1999 dan Implikasinya terhadap Otonomi Daerah dalam Kerangka Negara Kesatuan Republik Indonesia - Sudi Fahmi (Fakultas Hukum Universitas Islam Indonesia, 2001)
As a correction of local govemmerit regulation according to Law No. 5 1974 which is centralistic in nature, the advent of Law No. 22 1999 isexpected to blow the wind of change In the substance and the paradigm of the real autonomy. That is, the mechanismof decentralization system which guarantees (respects) the existence of local government Independence in regulating and arranging their home affairs and the dispersion ofnational revenue to local government for the even distribution of social justice. Never the less, the problems rises when the content of Law No 22 1999 runs against the amendment ofthe Constitution45, especially concerning article 18, article 18A, and article 18B. Namely, the confusion of decentralization which is placedas